UNDERSTANDING OF UDAKAVAHA SROTAS IN SHWASA ROGA - Teerthashree N S; Chetan M (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Srotas are the channels through which Sravana occurs. They are the pathways through which Rasa , Rakta etc Dhatus are transported .The body is represented by innumerable channels which has been given importance in both Swastha and Vyadhi. Shwasa is a disease which can manifest as both Swatantra Vyadhi and Paratantra Vyadhi. It is seen as Lakshana in many diseases like Vataja Apasmara,Kaphaja Udara etc and Upadrava in diseases like Atisara, Chardi,Thrushna etc. In Shwasa, there will be involvement of Pranavaha Srotas, Annavaha Srotas and Udakavaha Srotas. The Pranavaha and Annavaha Srotas are easily understandable in Shwasa. As the Pratyatma Lakshana of Shwasa i.e difficuly in breathing is directly relatable to Pranavaha Srotas and as it is Amashaya Samudbhava Vyadhi and there will be involvement of Agni in the pathogenesis.So, the Annavaha Srotas is also relatable. The Udakavaha Srotas cannot be directly understood in the pathogenesis. So, the Udakavaha Srotas are understood by comparing the Nidana, Lakshana and Chikitsa of Udakavaha SrotoDushti with the Shwasa.